An Improved Constant Voltage Based MPPT Technique for PMDC Motor - Mohammed Asim; Mohd Tariq; M.A. Mallick; Imtiaz Ashraf (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Stand-alone photovoltaic (SAPV) systems are being used in remote areas and are being seen as one of the promising solution in this regard. The SAPV system as presented in the paper consists of solar PV panel, a DC-DC converter, a controller and a PMDC motor. The current-voltage and power-voltage characteristics being nonlinear, the SAPV system require maximum power point techniques (MPPT) control techniques to extract maximum power available from the PV cell. A voltage based MPPT technique which is capable of tracking MPP has been selected because of numerous advantages it offers such as: simple and low cost of implementation. The limitation of constant voltage method is that its efficiency is low as the PV panel has to be disconnected from the load for measurement of the open circuit voltage (Voc). In the presented paper, the authors have removed this limitation by using a pilot PV panel for measurement of Voc. A proportional-integrator (PI) based controller is used in implementation of constant voltage MPP technique and the modeling is done in MATLAB®/SIMULINK simulation environment. The simulation results are presented and discussed in the paper, the results shows that the efficiency of the system has increased.